Role of religiosity, optimism, demographic characteristics and mental health problems among cancer patients - Qasir Abbas; Uzma Kanwal; Muhammad Umar Khan; Wizra Saeed; Mafia Shahzadi; Admin (Journal of the Pakistan Medical Association, 2020)
Abstract Objectives: The present study aims to investigate the role of religiosity, optimism, depression, death anxiety and differences in demographic characteristics among cancer patients. Methodology: The current study was completed in 12 months period from July 2018 to July 2019 in three different hospitals of Lahore and Faisalabad. After getting approval from the Institutional Review Board, a sample of N= 400 participants were collected. Only diagnosed patients of cancer with stage 1 and 2 were taken. In study t-test and one-way analysis of variance were used to investigate the findings. Results: Findings indicate a significant difference between cancer and non-cancer patients on the variables of religiosity, optimism, depression, and death anxiety. Significant gender differences were found on the variables of religiosity, depression and death anxiety and the insignificant difference was found on the construct of optimism among cancer patients. Moreover, cancer patients of rural and urban areas were found significantly different on the variables of religiosity, depression and death anxiety and the insignificant difference was found on optimism scale. Besides, there were found significant differences in death anxiety scale among cancer patients with a different type of cancer. Conclusion: It is concluded that there is a greater role of religiosity and optimism in controlling the level of depression and fear of death among cancer patients. Also, there is a meaningful role of gender, residential area, and types of cancer. Keywords: Religiosity; Optimism; Depression; Death Anxiety; Gender; Rural-Urban; Continuous....